Numerical Investigation of Helium Bubble Rising Behavior in Cross-Type Channel - Zeng, Chunjie; Yuan, Baoxin; Meng, Zhaoming; Zhang, Xin; Jiang, Herui; Mu, Defang; Yan, Ruihao (Frontiers in Energy Research, 2020)
In a certain nuclear reactor, the coolant channel is a cross-type channel. There is little research about bubble rising behavior in this kind of channel, but the neutron detection would be affected by the bubbles. Through comparing with previous experiment, proper numerical model has been determined, and the cross-type channel under different helium flow rates is studied with CFD software Fluent. Research shows that the bubble distribution exhibits some similarities under different helium flow rates, and the bubbles tend to rise near the tube wall; In the axial direction of the flow channel, the bubble coalescence can be observed, which leads the void fraction in the axial direction to increase first and then to be stable; The void fraction increases with increasing helium flow rates.